1996
DOI: 10.1248/bpb.19.962
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor-Promoting Activities of Triterpenoids from Ferns. I.

Abstract: To search for possible anti-tumor-promoters (cancer chemopreventive agents), we carried out primary screening of 23 triterpenoid hydrocarbons (1-23) isolated from ferns using an in vitro synergistic assay system. Of these triterpenoids, hop-17(21)-ene (2), neohop-13(18)-ene (3), neohop-12-ene (4), taraxerane (17), multiflor-9(11)-ene (18), multiflor-8-ene (19), glutin-5(10)-ene (21) and taraxastane (23) exhibited remarkable inhibitory effects on Epstein-Barr virus (EBV) activation induced by the tumor promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 0 publications
0
41
0
2
Order By: Relevance
“…These potencies were comparable to those reported for oleanolic acid 17) and the well-known anti-tumor promoting agent EGCG 12,18) ( Table 1). Although many types of triterpenoids such as taraxastane-, multiflorane-, cucurbitane-, and oleanane-type have been reported to show an inhibitory effect on EBV-EA activation, 17,[19][20][21][22] the effect of the oleanane-type related triterpenoids, 17,[20][21][22] including compounds 1 and 2, appears to be more potent than that of the multiflorane-and cucurbitane-type tripterpenoids. 19,22) Since the inhibitory effects on EBV-EA activation induced by TPA have been documented to correlate well with in vivo anti-tumor promoting activity, 15,17,20) the in vivo effect of 1, which is the most abundant ichthyotoxic substance, was then estimated using the two-stage carcinogenesis bioassay on mouse skin using DMBA as an initiator and TPA as a promotor.…”
Section: Resultsmentioning
confidence: 94%
“…These potencies were comparable to those reported for oleanolic acid 17) and the well-known anti-tumor promoting agent EGCG 12,18) ( Table 1). Although many types of triterpenoids such as taraxastane-, multiflorane-, cucurbitane-, and oleanane-type have been reported to show an inhibitory effect on EBV-EA activation, 17,[19][20][21][22] the effect of the oleanane-type related triterpenoids, 17,[20][21][22] including compounds 1 and 2, appears to be more potent than that of the multiflorane-and cucurbitane-type tripterpenoids. 19,22) Since the inhibitory effects on EBV-EA activation induced by TPA have been documented to correlate well with in vivo anti-tumor promoting activity, 15,17,20) the in vivo effect of 1, which is the most abundant ichthyotoxic substance, was then estimated using the two-stage carcinogenesis bioassay on mouse skin using DMBA as an initiator and TPA as a promotor.…”
Section: Resultsmentioning
confidence: 94%
“…show notable anti-cancer properties (Lai et al, 2010). The antithiamin substances in brackens, such as astragalin, isoquercitrin, rutin, caffeic acid, and tannic acid have Lee and Lin, 1988;Silva et al, 1995;Sun et al, 1997;Lee et al, 1999;Lin et al, 2000;Su et al, 2000;Chen et al, 2005b;Gao et al, 2007;Li J et al, 2014;Li S 2014;Elda et al, 2015 35 Guha et al, 1996 MTT: 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (Konoshima et al, 1996). A. evecta and Selaginella tamariscina have been shown to have significant antidiabetic activity (Miao et al, 1996;Nguyen, 2005).…”
Section: Anti-cancer Antidiabetic and Antiviral Activitymentioning
confidence: 99%
“…To establish an allograft colon carcinoma animal model, 5x10 5 CT-26 cells in 200 µl PBS were injected into the right flank of BALB/c mice. The tumors were allowed to grow into visible masses for 7 days, after which animals were divided into groups of 5 mice each.…”
Section: Extraction and Isolation Of Calenduloside E 6'-methyl Estermentioning
confidence: 99%
“…Certain natural triterpenoids, including oleanolic acid (3β-hydroxyolean-12-en-28-oic acid) and its isomer ursolic acid (3β-hydroxy-urs-12-en-28-oic acid), possess anti-cancer and anti-inflammatory activities (4)(5)(6)(7). Moreover, results of previous studies showed that several synthetic triterpenoid compounds derived from oleanolic acid including 2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oic acid (CDDO) and its methyl ester (CDDO-Me) derivative possess significant anti-tumorigenic and anti-inflammatory activity (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%